2018
DOI: 10.1002/jclp.22634
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of randomized trials of mind‐body interventions for PTSD

Abstract: Although many studies are limited by methodologic weaknesses, recent studies have increased rigor and, in aggregate, the results for mindfulness, yoga, and relaxation are promising. Recommendations for design of future mind-body trials are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 80 publications
2
31
0
1
Order By: Relevance
“…The online Supplementary Material 1 shows the full electronic search strategy for MEDLINE (via PubMed). We also included additional records identified through other sources, such as the reference lists of earlier reviews and meta-analyses related to the use of meditation and/or relaxation interventions to reduce anxiety (Delmonte, 1985; Eppley et al ., 1989; Krisanaprakornkit et al ., 2006; Manzoni et al ., 2008; Ospina et al ., 2008; Davis and Kurzban, 2012; Bolognesi et al ., 2014; Goyal et al ., 2014; Orme-Johnson and Barnes, 2014; Hilton et al ., 2017; Cushing and Braun, 2018; Goldberg et al ., 2018; Niles et al ., 2018), as well as from the reference list of the included primary studies. The deadline for the search was 13 July 2018.…”
Section: Methodsmentioning
confidence: 99%
“…The online Supplementary Material 1 shows the full electronic search strategy for MEDLINE (via PubMed). We also included additional records identified through other sources, such as the reference lists of earlier reviews and meta-analyses related to the use of meditation and/or relaxation interventions to reduce anxiety (Delmonte, 1985; Eppley et al ., 1989; Krisanaprakornkit et al ., 2006; Manzoni et al ., 2008; Ospina et al ., 2008; Davis and Kurzban, 2012; Bolognesi et al ., 2014; Goyal et al ., 2014; Orme-Johnson and Barnes, 2014; Hilton et al ., 2017; Cushing and Braun, 2018; Goldberg et al ., 2018; Niles et al ., 2018), as well as from the reference list of the included primary studies. The deadline for the search was 13 July 2018.…”
Section: Methodsmentioning
confidence: 99%
“… 28 Other systematic reviews reported similar findings, where they reported MBIs such as mindfulness, yoga and relaxation studies maybe useful for the mind–body treatments for PTSD but many of the trials suffered from methodologic weaknesses or were of low to moderate methodological rigor. 29 , 30 Further high-quality studies are needed on MBIs among PTSD-diagnosed participants in order to increase confidence in its effectiveness.…”
Section: Effects On Mental Healthmentioning
confidence: 99%
“…Previous studies have shown that AMBT had certain therapeutic effects for those suffering from PTSD (Van der Kolk et al, 2014;Polusny et al, 2015;Duan-Porter et al, 2016;Possemato et al, 2016). Mindbody therapy can also alleviate the physical and psychological symptoms suffered by PTSD patients, allowing them to actively cope with pain and enhance their ability to practice healthy living habits (Possemato et al, 2016;Niles et al, 2018). In addition, these self-help physical and mental interventions can help HWs take their attention off stressors and initiate an active health enhancement cycle (Niles et al, 2018).…”
Section: Improving the Mental Health Of Healthcare Workers By Interventionsmentioning
confidence: 99%